Possibilities of disposing silica fume and waste glass powder, which are environmental wastes, by using as a substitute for Portland cement - Bayraktar, Oguzhan Yavuz (Springer Science and Business Media LLC, 2021)
In this study, the possibilities of disposal of environmental waste, silica fume, and waste glass powder as substitutes in the mortar samples in Portland cement were investigated. For this purpose, Portland cement (CEM I), silica fume (SF), waste glass powder (WGP), CEN standard sand, and water were used in mortar production. Additive cements were obtained by using the SF, WGP, and SFWGP substitution methods in Portland cement at the rates of 10, 20, 30, and 40%. The flexural strength, compressive strength, radiation permeability (determination of linear absorption coefficient), high temperature, and alkali-silica reaction (ASR) effect on SF, WGP, and SFWGP were examined and compared with the control PC 42.5R samples. Mortar samples of 40 × 40 × 160 mm size were obtained with the grouts/mortars produced, and the samples were exposed to five temperature effects, namely, 20, 150, 300, 700, and 1000 ° C. Samples kept at 20 ° C are accepted as baseline. A total of 429 samples were studied, including the cooling process in the air (spontaneously in the laboratory, 20 ° C ± 2). After the samples achieved room temperature, flexural and compressive strength tests were carried out at 28 and 90 days. Test results demonstrate that SF, WGP, and SFWGP, which are environmental wastes, can be disposed both as a pozzolanic additive material both alone and together in cement mortars, can be utilized in buildings with high fire hazard, and the sample with the highest linear absorption coefficient is the sample obtained with SFWGP, and also, the expansion values ​​that occur in SF and WGP are less than the control sample.
Keywords: Compressive Strength; Construction Materials; Glass; Powders; Silicon Dioxide; 6. Clean water; 12. Responsible consumption